Assessment Practices in Mathematics Courses: Towards Dialectical Positioning (Interdisciplinary Research in Education, 2019)
This article aims to explore the perception and practices of mathematics teachers on assessment system in mathematics courses. I adopted interpretive research approach. Three schools each from Gorkha, Nuwakot and Kaski district were selected for study.  Six students, three teachers, three head teachers, and three resource persons were the interviewees of the study. I observed classrooms and conducted FGDs for collecting textual information. The data was generated from these different sources of each school have been verified and critically analyzed through triangulation and generate themes. It was found that, existing assessment practices were formative assessments such as project work, class work, and homework, attendance, unit test, remedial support, extracurricular activities, field visit, group discussion, weekly tests and use of summative evaluation as a formative assessment tool.